Relentless - Greaney, Mark (New York : Berkley, 2021)
"The first agent's disappearance was a puzzle. The second was a mystery. The third was a conspiracy. Intelligence operatives around the world are disappearing. When a missing American agent reappears in Venezuela, Court Gentry, the Gray Man, is dispatched to bring him in. But a team of assassins has other ideas. Court escapes with his life and a vital piece of information. Meanwhile, CIA agent Zoya Zakharova is in Berlin. Her mission: to infiltrate a private intelligence firm with some alarming connections. The closer she gets to answers, the less likely she is to get out alive. Court and Zoya are just two pieces on this international chessboard, and they're about to discover one undeniable truth-sometimes capturing a king requires sacrificing some pawns"--
"#1 New York Times bestselling author of ONe Minute Out"--Duat jacket
Keywords: Spy stories; Suspense fiction